Cytotoxic activity screening of some medicinal plants from south of Iran - S. Esmaeili; M. Hamzeloo-Moghadam; S. Ghaffari; M. Mosaddegh (Iranian Society of Pharmacognosy, 2014)
Background and objectives: Cancer is a public health problem all over the world. Herbal medicines have a vital role in the prevention and treatment of cancer and large numbers of plants and their isolated constituents have shown potential anticancer activity. Methods: Twenty seven medicinal plants from southern Iran provinces have been extracted with methanol and screened for their cytotoxic activity against MCF-7, WEHI-164, HepG-2, MDBK and A-549 cell lines by MTT assay. Results: The methanol extracts of two species, Calotropis procera andJuniperus excelsa, demonstrated to be more effective compared to other extracts. Conclusion: The above species are proper candidates for further cancer studies.